Evaluation of Efectivity, Relevancy, And Sustainability on Project Second Water Sanitation For Low Income Communities (WSLIC-2) - Sita, Rai; Agusta, Ivanovich (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2011)
The aim of this research are to evaluate how far the Second Water Sanitation for Low Income Communities (WSLIC-2) project appropriate with empowerment concept and to evaluate effectiveness, relevance, and sustainability impact of WSLIC-2 project which implemented in Pangradin village. Empowerment concept that used to analyze WSLIC-2 project design and its implementation in field are 10 principles Community Driven Development (CDD). As a project which based on community, WSLIC-2 project design has appropriated with 10 principles of CDD. The principles of CDD which related to concept of plan and construction phase has implemented well in the field. But, the principle who related with concept of maintenances phase not yet implemented well in field. In general, WSLIC-2 project that conducted in Pangradin village assessed quite relevance, but not fully effective and the sustainability is still questionable. Optimization activity of CLTS and strengthening structure of UPS are implementable in order to create a sustainable WSLIC-2 project.